Molecular dissection of the valproic acid effects on glioma cells - Hoja, Sabine; Schulze, Markus; Rehli, Michael; Proescholdt, Martin; Herold-Mende, Christel; Hau, Peter; Riemenschneider, Markus J. (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.11379 Sabine Hoja, Markus Schulze, Michael Rehli, Martin Proescholdt, Christel Herold-Mende, Peter Hau, Markus J. Riemenschneider